Reflective Pedagogy: Case Study of Organic Chemistry at the University of Muhammadiyah Semarang - Eko Yuliyanto; Fitria Fatichatul Hidayah; Enade Perdana Istyastono; Yosef Wijoyo; Titien Siwi Hartayu (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The development of the modern age is a lot of changes in education is the paradigm of teacher-centered learninginto student-centered learning which has a very important role in maximizing its competence in classroom management. One of the lessons in chemistry education that has problems is organic chemistry courses. Based onthe reflections applied to teachers and students "What has been gained from the learning process?", "What is thevalue obtained while the process is underway?" And "What will be done next (implementation)?". The results arestill very unsatisfactory, this is due to the limited ability of lecturers in the learning process. Associated with these conditions, then of course required intensive changes and planned for comprehensive improvement associated with the input to be generated. Efforts to be made is to improve the paradigm of learning. The selected learning paradigm is Reflective Pedagogy Paradigm (PPR). Reflective Pedagogy Paradigm was chosen because based on the results of research can improve the performance of lecturers in teaching, improve the readiness of lecturers in teaching, and make students able to reflect the learning process, and students become more active. The research was conducted following a workshop with lecturers who have implemented Reflective Pedagogy at Sanata Dharma University Yogyakarta. Stages in Reflective Pedagogy are context, experience, reflection, action and evaluation. It is expected by the end of two meetings. To be able to apply PPR, a lecturer needs to be equipped with special training on PPR-based teaching strategies as well asreflection skills (ICAJE, 1993, Gwaza et al., 2010; Schaub-de Jong dkk.2011; Wijoyo et al., 2016). Based on the results of the teacher reflection, it is increasingly realized that the preparation of learningis very important, and it is realized. While based on the results of reflection students stated that the purpose oflearning is clear, the material relevant to the profession of students, and understanding of the material becomeseasier, and the moral values for students. This case study is also in line with previous research that John Dewey(1933), He argued that learning from experience is enriched by reflecting on experience and Donald A. Schön (1987) theorized that reflective practice represents an important factor to improve professional activity. Jack Mezirow, (1991, 2000) gives reflection a central role in learning because through it we become aware of the ways in which we interpret reality and give meaning to actions and behavior. Writing-to-learn tasks should encourage students to conceptualize writing in a way that emphasizes exploration, expressive inquiry, discovery, problem-solving, decision making and knowledge construction.Key Word: Reflective Pedagogy Paradigm, case study, Organic Subject